In vivo/in vitro evaluation of the antioxidant capacity of LECISAN - Leidys Cala Calviño; Haydée Cruz Vadell; Yaixa Beltrán Delgado; David Garrido Larramendi; Onel Fong Lores (Universidad de Ciencias Médicas de La Habana, 2023)
Introduction: Soy lecithin is a highly demanded dietary supplement, with supposed benefits as antioxidants based on its high fatty acid content. Objective: To determine the preclinical effect of soy lecithin on the oxidative status of Wistar rats and on human erythrocytes as an in vitro pharmacological biomodel. Material and Methods: An experimental non-clinical pharmacology study was carried out to determine the oxidative profile in Wistar rats after the administration of soy lecithin in maximum and minimum doses, and to compare the effects with the non-supplemented control group. Subsequently, a prospective, experimental and non-clinical pharmacological study was carried out in human erythrocytes as a pharmacological biomodel according to the hemolysis test, with three experimental groups at different concentrations of the test product, a positive control and a negative control. The differences between the experimental groups were evidenced by the Kruskal Wallis ANOVA test and Dunn's post hoc test with a significance level of less than 5%. Results: In vivo oxidative stress markers were reduced in the administration groups, becoming more evident at higher doses, with a tendency towards stability in catalase values. The soy lecithin used showed signs of hemolysis, and the optical microscopy study showed severe morphological damage in the erythrocytes additionally treated with the tested product and H2O2. Conclusions: The results obtained suggest the existence of a pro-oxidant effect by inducing oxidative stress in vivo and erythrocyte hemolysis in vitro.